Elder Abuse in Malaysia: Issues and Challenges - Asiah, Bidin; Zulkifli, Mohd; Jal Zabdi, Mohd Yusoff (2016)
Elder abuse and neglect have been recognized as social and health problems affecting significant numbers of elderly persons in many western countries. In fact in some countries, they have been considered as a crime. Even though the subject of elder abuse has gained prominence in the past two decades, in Malaysia it is relatively a new issue. This study aims to highlight the scenario of abuse of the elderly in Malaysian society and some of the issues and challenges pertaining to it. The data collected from various documents, unpublished reports and interview with officers from the Department of Social Welfare revealed that local information on this subject is scarce. The incidents of abuse normally take place within the secrecy, thus it is often hidden from the public, seldom reported, and under-recognized. The elderly victims are unlikely to report against their own families for fear of embarrassment and losing care support. Lack of awareness of support services may also be a contributory factor. Lastly, few recommendations will be addressed so as to make this issue as an issue of a public concern.